Enmienda al art. 208 de la Constitución de la República del Ecuador en relación a los deberes y atribuciones del consejo de participación ciudadana y control social - Parreño Ruiz, Wilson Rodrigo (2015)
The Ecuador is a state of rights and social justice as determined by its Art. 1, also set among its features is a democratic state, a concept that has had a wide variety of notions and interpretations, all tending to establish that the democratic system calls for the active participation of the people in government decisions through participation mechanisms provided for in the constitution and the law, one's suffrage. . Our current Constitution of the Republic since October 20 of 2008 in its Article 204 recognizes two new functions of the state, the Transparency and Social Control and the Electoral Tribunal; our interest is in the first, being the need to review and analyze its connotation and significance in Ecuadorian society in order to focus some limitations and structural flaws of this new function; then transcribe the provisions of art. 204 of the Constitution: "Art. 204. The people are the principal and first auditor of public authority in the exercise of their right to participation. The Transparency and Social Control promote and encourage control of institutions and public sector organizations, and natural or legal private sector who provide services or perform activities of public interest people for conduct with accountability, transparency and equity; foster and encourage citizen participation; will protect the exercise and enforcement of rights; and prevent and combat corruption. The Transparency and Social Control shall consist of the Council of Citizen Participation and Social Control, the Ombudsman, the Comptroller General and the superintendents. These entities have legal personality and administrative, financial, budgetary and organizational autonomy. " From this perspective we can see that all the institutions of this function, the Council of Citizen Participation and Social Control is the body with more constraints and limited powers, so that its field of action and intervention is merely preventive, informative, what which is insufficient in its aim of preventing acts of corruption within public institutions in Ecuador. Because of this, consider essential to review the regulatory framework concerning the powers and authority of the Council for Citizen Participation and Social Control and strengthen the scope of their activities, incorporating type sanctioning powers in order to promote citizen participation, encourage deliberative processes public and promote training in citizenship, values, transparency and anti-corruption